Ecofeminist Poetry as Living on Earth with Attention and Care - Vincent, Esther Xueming (The Trumpeter)

(untitled) (Athabasca University Press, 2022)
The article explores ecofeminism as intersectional, founded upon a politics of relations. Through an ecofeminist re-reading of Eavan Boland’s “Anna Liffey” and Grace Nichols’ “Hurricane Hits England”, the article discusses how these women poets remake geographies to locate themselves in time and place as kin to other person-beings.